Tracing a pollinator’s path - Laura Boffi (Ecology and Society, 2024)
This paper describes Percorso Impollinatori (Tracing a Pollinator’s Path), a transdisciplinary citizen engagement project aiming to address the decline of wild pollinating insects via material deliberation methods. Following a participatory design approach, three different participatory actions were co-designed and prototyped in two locations in Italy as experimental instances of material deliberation methods, incorporating citizens, farmers, scientific experts, and artistic professionals into collaborative assemblages. This project identified material deliberation as a way to address epistemic pluralism, meaning that the non-discursive, artistic, and embodied modes of knowing were applied in combination with the more formal, scientific disciplines. Three participatory actions were specifically meant for the collaboration of local citizens and farmers, aiming: (1) to reflect on their personal experiences of pollinators and pollination, (2) to rethink the values they attribute to such experiences and to pollination services, (3) to reframe the pollinator decline issue from locally focused ecological and cultural perspectives, and (4) to generate collaborative ideas to invert the decline and let pollinating insects thrive. Drawing from Lattanzi’s definition of transdisciplinarity as disciplinary “outerspace” and anthropologist Ingold’s concept of correspondence, I (as the leading researcher and project designer) reflect on the collaborative assemblages constructed for each participatory action and on the dynamics enabled among their members, which allowed the emergence of transdisciplinary outcomes. I describe the participatory actions, focusing on how each unfolded through a preparatory and enactment phase, and the learning collected from each one. I conclude by suggesting that both in the preparation and in the enactment of the material deliberation methods, the activation of correspondence dynamics within the collaborative assemblages elicited the emergence of transdisciplinarity around the issue of pollinator decline. Future researchers are invited to reiterate the design and implementation process in other complex and conflictual sustainability contexts.